Turtles are Surprisingly Fast Swimmers - Miki, Satoshi; Kobayashi, Gen; Ueno, Juri; Aoi, Yû; Iwamatsu, Ryô (Third Window Films, 2009)
Suzume Katakura is an ordinary housewife. Her husband has been sent overseas on business, and although he phones her regularly, he is more concerned with the heath and welfare of his pet turtle. The days pass monotonously; it is though no one pays her any attention, not even her husband. The ordinariness of her life is interrupted one day when she spots a flyer in a stairway advertising for spies. Intrigued, Suzume phones the number. Three days later she is instructed to go to a run down apartment. She is greeted by a man and woman, he is unemployed, she is a shopping mall announcer. They claim to be working for a foreign state, and just like Suzume they are ordinary people with ordinary lives. The couple persuade Suzume to become a secret agent too. They virtually force 5 million yen onto Suzume, and so begins her life as a spy! [Cover]